Assessing the health impact of intervention in supermarket bakeries using fractional exhaled nitric oxide (FeNO) and other clinical endpoints for baker’s allergy and asthma - Al-Badri, Faisal (Department of Public Health and Family Medicine, 2019)
Aim: To assess the health impact of an intervention in supermarket bakeries using fractional exhaled nitric oxide and other clinical endpoints for baker’s allergy and asthma after a one-year follow-up period. Methods: A field randomised controlled trial of 31 bakeries initially assigned to one of two intervention groups (bakery mixer lid and training) (n=244) and a control group (n=93). Health data prior to and after the intervention included a modified ECRHS questionnaire; Phadiatop ® and serum specific IgE to cereal flours (wheat, rye, alpha-amylase); and FeNO performed during the work shift using NIOX MINO®. The data of the two intervention groups was combined into one intervention group for the analysis. Data was analysed using STATA (version 12). Results: The two groups were comparable with regard to age (32-33 years), proportion of females (55%-57%) and smoking status (38%-40%). The intervention group had a significantly higher prevalence of workers with atopy (42%, p=0.025), work-related chest symptoms (25%, p=0.044) and sensitisation to cereal flour allergens (35%, p=0.042) at baseline than the control group (25%, 15%, 23% respectively). At one year of follow-up, the incidence and level of decline of work-related ocular-nasal and chest symptoms, sensitisation status and elevated FeNO (FeNO >25ppb) was similar in the two groups. The mean difference in FeNO was similar across the two groups (2.2ppb vs 1.7ppb, p=0.860). However, when stratifying according to baseline FeNO >25ppb, the FeNO decline was greater in the intervention group (16.9 ppb) than in the control group (7.7ppb), although not statistically significant (p=0.237). Multivariate logistic regression models (adjusting for smoking, baseline sensitisation to cereal flour, baseline FeNO >25ppb) did not demonstrate an appreciable decline in FeNO (>10%) in the intervention compared to the control group. However, stratification according to the presence of work related ocular-nasal symptoms at baseline demonstrated a significant decline (>10%) in FeNO in the intervention group compared to the control group (OR=3.73, CI: 1.22-11.42). Conclusion: This study demonstrates some evidence of an intervention effect on exhaled nitric oxide (FeNO) one year after the intervention, particularly among bakers reporting work-related ocular-nasal symptoms at baseline. The lack of a demonstrably stronger effect on other clinical endpoints can be attributable to the short follow-up period.